Structural and functional characterization of β2‐glycoprotein I domain 1 in anti‐melanoma cell migration. Issue 6 (15th May 2019) - Leu, Shr‐Jeng Jim; Lee, Tzong‐Yi; Cheng, Shu‐Wei; Tsai, Meng‐Ying; Lin, Yu‐Shan; Chiou, Tzeon‐Jye; Huang, Kai‐Yao; Chiang, An‐Na
Abstract: We previously found that circulating β2 ‐glycoprotein I inhibits human endothelial cell migration, proliferation, and angiogenesis by diverse mechanisms. In the present study, we investigated the antitumor activities of β2 ‐glycoprotein I using structure‐function analysis and mapped the critical region within the β2 ‐glycoprotein I peptide sequence that mediates anticancer effects. We constructed recombinant cDNA and purified different β2 ‐glycoprotein I polypeptide domains using a baculovirus expression system. We found that purified β2 ‐glycoprotein I, as well as recombinant β2 ‐glycoprotein I full‐length (D12345), polypeptide domains I‐IV (D1234), and polypeptide domain I (D1) significantly inhibited melanoma cell migration, proliferation and invasion. Western blot analyses were used to determine the dysregulated expression of proteins essential for intracellular signaling pathways in B16‐F10 treated with β2 ‐glycoprotein I and variant recombinant polypeptides. Using a melanoma mouse model, we found that D1 polypeptide showed stronger potency in suppressing tumor growth. Structural analysis showed that fragments A and B within domain I would be the critical regions responsible for antitumor activity. Annexin A2 was identified as the counterpart molecule for β2 ‐glycoprotein I by immunofluorescence and coimmunoprecipitation assays. Interaction between specific amino acids of β2 ‐glycoprotein I D1 and annexin A2 was later evaluated by the molecular docking approach. Moreover, five amino acid residues were selected from fragments A and B for functional evaluation using site‐directed mutagenesis, and P11A, M42A, and I55P mutations were shown to disrupt the anti‐melanoma cell migration ability of β2 ‐glycoprotein I. This is the first study to show the therapeutic potential of β2 ‐glycoprotein I D1 in the treatment of melanoma progression. Abstract : In this study, we investigated the antitumor activities of β2‐GPI using structure‐function analysis and mapped the critical region and amino acid residues that mediate its anticancer effects.